Windscreens as sites of competing Turkish nationalisms: Kemalists vs. Islamists - Aysun Akan (Studies on National Movements, 2023)
In Turkey, the dominant political ideology is nationalism, but there are different variants competing for influence. Kemalism, the philosophy that laid the foundations for modern Turkey, advocated for a top-down modernization and secularisation of society, but also crucially involved creating a modern western-style nation state. The decades of the 1920s and 1930s saw the establishment of Kemalism as the official state ideology. Until the late 1990s, Kemalism remained as the state ideology, despite being challenged by a wide range of political tendencies. The greatest and most serious threat has come from political Islam, which rejects key tenets of the Kemalist ideology, namely western modernization and secularism. Conflict between Kemalists and Islamists on the national level has simmered since the 1970s, but a defining moment occurred in 2002 with the electoral victory of the Justice and Development Party (Adalet ve Kalkınma Partisi, AKP). Over a period of 20 years in power, the AKP has eliminated much of the Kemalist improvements to Turkey's state institutions, society and culture. The result of the AKP’s Islamic nationalist policies has been increased political polarisation and friction in Turkish politics and society. This political polarisation led to an unusual practice in everyday politics; supporters on both sides manifest their respective ideologies via stickers with political messages displayed on the rear windscreens of cars as a challenge to the opposing ideology. Based on the findings of interviews conducted with owners of cars displaying these messages, this study aims to analyse the meaning of this practice in relation to everyday nationalism, and its implications for Turkish politics at large.